PLD.24 Gene expression profiling of human decidua during term labour: inflammation as a key driver of labour. (9th June 2014) - Stephen, GL; Lui, S; Hamilton, SA; Stevens, A; Jones, RL
Abstract : Background: There is accumulating evidence that sterile inflammation is a driver of labour in myometrium and cervix; however the involvement of the decidua is poorly defined. Our previous studies report decidual leukocyte infiltration prior to and during labour. The current study aimed to characterise the inflammatory gene profile in the decidua during term labour. Methods: Decidua was obtained from two groups (no labour and term labour); pooled RNA was applied to Human Genome U133 Plus 2.0 Affymetrix GeneChips. Bioinformatic and pathway analysis was performed using Ingenuity pathway analysis (IPA), with gene validation by real time PCR. Results: Affymetrix analysis identified widespread changes in decidual gene expression following labour. The most highly altered biological functions included: haematological system function, cell-cell signalling, immune cell trafficking, cellular movement and inflammatory responses; however those involved in tissue morphology, metabolism and cell survival were also altered. PCR validation was selected based on fold change and functional significance: ICAM (p = 0.006), CXCR4 (p = 0.017), CD44 (p = 0.02), TLR 4 (p = 0.035), SOCS3 (p = 0.02), BCL2A (p = 0.018) and IDO1 (p = 0.029) were upregulated following labour. Transcription factors predicted, from the gene array, as potential upstream regulators were: NFkB, RELA, STAT1 (Signal transducer and activator of transcription 1) and MEOX2 (mesenchyme homeobox 2) Conclusions: This study provides further evidence of non-infection related inflammatory pathways contributing to term labour, in particular identifying inflammatory changes in the decidua similar to those in myometrium and cervix. Ongoing studies focus on identifying potential targets to suppress decidual inflammation as a potential means of arresting labour.